How Nurses Maintain High‐Risk Medication Safety in Paediatric Intensive Care - Meng Huang; Meng Lv; Jiayu Huang; Yan Lin (Nursing in Critical Care, 2026)
ABSTRACT Background Existing research has focused mainly on high‐risk medication errors, contributory factors and process‐based interventions; less is known about nurses' everyday safety work in paediatric intensive care. Aim To explore how nurses maintain high‐risk medication safety in paediatric intensive care. Study Design A descriptive qualitative study using purposive sampling, critical incident interviews and inductive content analysis at a tertiary children's hospital in China. Results Ten nurses participated. Four themes were generated: anomaly recognition and proactive verification; team communication and continued follow‐up after risk identification; safety checks and bedside adaptations in medication practice; and learning from near misses and adjusting future practice. Together, these practices spanned order review, preparation, administration, pump and compatibility management, monitoring and team learning. Conclusions Experienced nurses in paediatric intensive care maintained high‐risk medication safety through linked practices of anomaly recognition, proactive verification, team communication, continued follow‐up, safety checks, bedside adaptation and near‐miss learning. Relevance to Clinical Practice Training and workflow support should strengthen anomaly recognition, dose and infusion‐rate recalculation, communication, active double checking, compatibility checking, infusion‐pump management, follow‐up monitoring and near‐miss learning.